Introduction of an Efficient Method for the Observation of Living Paramecium - Yang, Xianyu; Gao, Xin (IJRDO- Journal of Educational Research, 2018)
Fast movement of living Paramecium makes its observation very difficult and low efficiency of taking pictures. Volume-fixing method being reported on Chinese local journals could solve this problem completely. To popularize this method, we will simply introduce this method here .